Development of a numerical tool for the seismic vulnerability assessment of vernacular architecture - Ortega, Javier (2022)
Aiming at protecting the vernacular heritage located in earthquake prone areas, the paper presents the development and validation of the numerical tool that constitutes the core of a novel seismic vulnerability assessment method: Seismic Assessment of the Vulnerability of Vernacular Architecture Structures (SAVVAS). An extensive numerical modeling campaign was carried out to evaluate and quantify the influence of several parameters on the seismic response of vernacular buildings. The results were compiled into a database on which regression analysis could be performed to extract correlations between seismic capacity and qualitative and simple quantitative data that can be obtained from visual inspection.